2023
DOI: 10.2106/jbjs.oa.23.00004
|View full text |Cite
|
Sign up to set email alerts
|

Exponential Growth in Female Residency Applicants in Orthopaedic Surgery Over the Past 15 Years

Abstract: Introduction: Orthopaedic surgery is recognized as one of the most popular but least diverse medical subspecialties.Although significant efforts have been made in recent years to improve gender diversity, orthopaedic surgery continues to lag behind other surgical subspecialties. A recent study predicted that it would take 217 years for orthopaedic surgery to reach gender parity matching the 36.3% of practicing female physicians in the United States. The purpose of our study was to evaluate the annual percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This has also resulted in an increasingly diverse active resident class at 5.1% African American, 7.4% Hispanic/LatinX, and 13.3% Asian and recently graduated orthopaedic surgeons at 3.7% African American, 5.1% Hispanic/LatinX, and 12.4% Asian. 16 Unfortunately, there were significant declines in active residents among Native American and Hawaiian/Pacific Islander populations, with decreases of 0.06% and 0.002%, respectively. Additionally, there were no Native American recently graduated attendings, and only 0.02% of attendings were Hawaiian/Pacific Islander, highlighting the substantial representation gap for these communities and underscoring the urgent need for targeted efforts in this area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has also resulted in an increasingly diverse active resident class at 5.1% African American, 7.4% Hispanic/LatinX, and 13.3% Asian and recently graduated orthopaedic surgeons at 3.7% African American, 5.1% Hispanic/LatinX, and 12.4% Asian. 16 Unfortunately, there were significant declines in active residents among Native American and Hawaiian/Pacific Islander populations, with decreases of 0.06% and 0.002%, respectively. Additionally, there were no Native American recently graduated attendings, and only 0.02% of attendings were Hawaiian/Pacific Islander, highlighting the substantial representation gap for these communities and underscoring the urgent need for targeted efforts in this area.…”
Section: Discussionmentioning
confidence: 99%
“…This likely has cumulated into more female applicants at 23%, residents at 20%, and recently graduated female orthopaedic surgeons at 22% as reported by the ACGME and others (new ACGME fellows were a surrogate used for recent graduates). 15,16…”
Section: Discussionmentioning
confidence: 99%
“…Given the increasing diversity in orthopedic surgery, including the number of women entering the field, 8 we need to better understand the demographic details of the orthopedic workforce and what leads to, or prevents, orthopedic surgeons from practicing in rural communities. Our analysis of MasterFile and AHRF data found that while the number of women orthopedic surgeons in active practice in Kansas more than doubled from 2009 to 2019, this translated to women comprising only 3.7% of the active orthopedic surgery workforce in the state by 2019.…”
Section: Discussionmentioning
confidence: 99%
“… 5 In addition, while more women are entering the practice of orthopedic surgery (women represented 6.0% of orthopedic surgeons in 2010 and 7.4% by 2022), available data regarding physician distribution have not looked at the gender composition of the orthopedic surgeon workforce by rurality in Kansas. 8 10 …”
Section: Introductionmentioning
confidence: 99%
“…This number is higher than the latest estimates of the percentage of active female physicians in surgery specialties (range 6% to 23%). 19 Despite ∼70% of female respondents reporting confidence in becoming a surgeon, only 33% perceived the field to be inclusive vs over 50% of male respondents. This perceived lack of inclusivity may have also contributed to the disparate number of surgical shadowing hours—and total shadowing hours—reported by males and females, in which males obtained considerably more hours than females ( P < .05).…”
Section: Discussionmentioning
confidence: 99%